Profile of students’ Physics Problem Solving Skills and Implementation PBL Model Assisted by 3D Digital Module to Improve Problem Solving Skills - Kinasih, Rachmadaniz Audrey; Prahani, Binar Kurnia; Wibowo, Firmanul Catur; Costu, Bayram (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
The aim of this research is to analyze high school students' ability to solve physics problems as a consideration for implementing the PBL learning model assisted by Android-based 3D digital modules. The research method uses descriptive qualitative analysis techniques to find out information about a problem the facts face. The research was conducted at SMA Nahdlatul Ulama 1 Gresik with 160 students as respondents. Data obtained from research respondents were categorized into three groups, namely low (score 0-40), medium (score 41-70) and high (score 71-100). From the research results, there were 154 students in the low category, while there were 5 students in the medium category and 1 person in the high category. The conclusion is that students' ability to solve physics problems is still low and needs to be improved, so it is necessary to provide innovative learning models and media, one of which can be done by implementing PBL models and media in the form of Android-based 3D digital modules which will make students more interested in learning so that helps hone physics problem solving skills.